Research on the Method of Ground Stress Balance under Complex Conditions Based on Geometric Tracing - Ge Wang (Advances in Civil Engineering)
The accuracy of the initial ground stress balance determines the accuracy of the finite element analysis of geotechnical problems. The traditional ground stress balance method has a good balance effect for simple geotechnical models but has strong limitations when the structure and soil interact with each other, the geometry of the model is complex, or the constraints are complicated. To deal with such problems, this paper proposes a general ground stress balance method based on geometric tracing by iteratively superimposing the static displacement field of the numerical model with the initial node coordinates of the numerical model. Two commonly used methods as well as the proposed method were tested with a model which contains both soil elements and structural elements and a case study. Test results show that the proposed method is capable of dealing with a complex model in which the commonly used methods fail to. Furthermore, the proposed ground stress balance method was demonstrated to be clear and has rapid convergence and high accuracy for complex stratum-structure geotechnical problems.